Low-cycle full-field residual strains in cortical bone and their influence on tissue fracture evaluated via in situ stepwise and continuous X-ray computed tomography - Hari Arora (Journal of Biomechanics, 2020)
As a composite material, the mechanical properties of bone are highly dependent on its hierarchical organisation, thus, macroscopic mechanical properties are dictated by local phenomena, such as microdamage resulting from repetitive cyclic loading of daily activities. Such microdamage is associated with plastic deformation and appears as a gradual accumulation of residual strains. The aim of this study is to investigate local residual strains in cortical bone tissue following compressive cyclic loading, using in situ X-ray computed tomography (XCT) and digital volume correlation (DVC) to provide a deeper insight on the three-dimensional (3D) relationship between residual strain accumulation, cortical bone microstructure and failure patterns. Through a progressive in situ XCT loading–unloading scheme, localisation of local residual strains was observed in highly compressed regions. In addition, a multi-scale in situ XCT cyclic test highlighted the differences on residual strain distribution at the microscale and tissue level, where high strains were observed in regions with the thinnest vascular canals and predicted the failure location following overloading. Finally, through a continuous in situ XCT compression test of cycled specimens, the full-field strain evolution and failure pattern indicated the reduced ability of bone to plastically deform after damage accumulation due to high number of cyclic loads. Altogether, the novel experimental methods employed in this study, combining high-resolution in situ XCT mechanics and DVC, showed a great potential to investigate 3D full-field residual strain development under repetitive loading and its complex interaction with bone microstructure, microdamage and fracture.